Coming down the "chimney": Percutaneous coronary intervention on a post‐transcatheter aortic valve replacement with valve‐in‐valve patient. Issue 10 (8th October 2022) - Taleb, Adam
Abstract: Accessing the coronary arteries post‐transcatheter aortic valve replacement is a growing challenge. This is a case of a patient requiring percutaneous coronary intervention on a left circumflex artery after a TAVR valve‐in‐valve and a left main "chimney" stent, describing all the challenges met during the procedure. Abstract : Accessing the coronary arteries post transcatheter aortic valve replacement is a growing challenge. This is a case of a patient requiring percutaneous coronary intervention on a left circumflex artery after a TAVR valve‐in‐valve and a left main "chimney" stent to prevent coronary occlusion were performed.